2022
DOI: 10.1002/hyp.14703
|View full text |Cite
|
Sign up to set email alerts
|

On (in)validating environmental models. 2. Implementation of a Turing‐like test to modelling hydrological processes

Abstract: Part 1 of this study discussed the concept of using a form of Turing‐like test for model evaluation, together with eight principles for implementing such an approach. In this part, the framing of fitness‐for‐purpose as a Turing‐like test is discussed, together with an example application of trying to assess whether a rainfall‐runoff model might be an adequate representation of the discharge response in a catchment for predicting future natural flood management scenarios. It is shown that the variation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 132 publications
(177 reference statements)
1
17
0
Order By: Relevance
“…The estimation of RCs for the Kent catchment was made using the method of Beven (2019) for calculating ‘event discharge’ which is most applicable to fast‐responding catchments. This is the case because, in fast‐responding catchments it is possible estimate ‘event discharge’ by using recession curve extrapolation using a master recession curve and hence calculate an event RC (Beven, 2019; Beven et al, 2022). Beven et al (2022) showed that the RCs for the Kent catchment (where rainfall was initially interpolated using the Thiessen Polygon method ) may have RCs greater than 1 (i.e., more event discharge than apparent event rainfall).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of RCs for the Kent catchment was made using the method of Beven (2019) for calculating ‘event discharge’ which is most applicable to fast‐responding catchments. This is the case because, in fast‐responding catchments it is possible estimate ‘event discharge’ by using recession curve extrapolation using a master recession curve and hence calculate an event RC (Beven, 2019; Beven et al, 2022). Beven et al (2022) showed that the RCs for the Kent catchment (where rainfall was initially interpolated using the Thiessen Polygon method ) may have RCs greater than 1 (i.e., more event discharge than apparent event rainfall).…”
Section: Resultsmentioning
confidence: 99%
“…This is the case because, in fast‐responding catchments it is possible estimate ‘event discharge’ by using recession curve extrapolation using a master recession curve and hence calculate an event RC (Beven, 2019; Beven et al, 2022). Beven et al (2022) showed that the RCs for the Kent catchment (where rainfall was initially interpolated using the Thiessen Polygon method ) may have RCs greater than 1 (i.e., more event discharge than apparent event rainfall). This was also the case for some of the largest events on record where the estimates of discharge might also depend on epistemic uncertainties in the rating curve extrapolation.…”
Section: Resultsmentioning
confidence: 99%
“…An application of this evaluation strategy to the River Kent catchment in Cumbria (UK) was presented in Beven et al (2022). The topic of that paper was the prediction of major flood peaks.…”
Section: Testing Models As Hypotheses: An Invalidation Approachmentioning
confidence: 99%
“…These runoff coefficients then reflect the potential epistemic errors in input and output volumes contained in the observations. A distribution of runoff coefficients for ‘similar’ events (estimated in Beven et al, 2022, on the basis of the nearest neighbours defined by event rainfall volume, antecedent flow and peak flow) then allows limits of acceptability to be defined for any particular event used to evaluate the model outputs.…”
Section: Testing Models As Hypotheses: An Invalidation Approachmentioning
confidence: 99%
See 1 more Smart Citation